Between other territories. From territories to inter-territories - GROSSO, José (Utopía y Praxis Latinoamericana, 2024)
In the dominant Western civilizational model, “development”, “language” and “critical thinking” constitute the commonsense plot of a linear, dizzying, and anthropic energy metabolism; in a growing and cumulative extractivism; working by inertia of an absolute and self-performative logic; under the biopolitical regime of an infinite agonizing “crisis”. Faced with this, Carlos Walter Porto-Gonçalves, starting from Geography and hand in hand with social movements and community struggles, defending their way of life, has moved to their other territories inhabited in human-non-human coexistence. In the push of that impulse, here I slip from territorial to inter-territorial senses.